ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA BERDASARKAN TEORI APOS DITINJAU DARI KEMANDIRIAN BELAJAR - Rahmawati, Ratih Yulinda; Khaerunnisa, Etika (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2022)
The purpose of this study is to analyze how the ability to understand students' mathematical concepts based on the APOS theory on the material of building blocks and cubes when viewed from the independence of students' learning. This research was conducted in class VIIIA SMPN 5 Cilegon. The research subjects were 6 students consisting of two students from each category of learning independence. This study uses a qualitative research type. The instruments used in this study were a learning independence questionnaire, a written test of understanding the concept consisting of 2 description questions and interviews. The data analysis used includes data reduction, data presentation, and drawing conclusions. In this study, the analysis of the level of understanding of students' mathematical concepts using the APOS theory which includes indicators of concept understanding. The results of this study state that students with high learning independence have the ability to understand mathematical concepts to the schema stage, students with moderate learning independence have mathematical problem solving abilities to the object stage, while students with low learning independence only have the ability to understand mathematical concepts to the stage of action only